Optimizing HR Management in BAZNAS: Evaluating the SIMBALite Application with the UTAUT 2 Model - Hadi, Abdul (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
This study examines the effectiveness and acceptance of the SIMBALite application developed for BAZNAS, utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) as the theoretical framework. The research aims to assess how factors such as Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions impact user satisfaction and technology adoption. A total of 44 respondents participated in the study, providing data through a structured questionnaire. The reliability of the measurement instrument was confirmed with a Cronbach’s Alpha of 0.943, indicating excellent internal consistency. Validity tests, using Pearson’s Product-Moment Correlation, validated all items with coefficients exceeding the critical value of 0.297. Descriptive and inferential statistical analyses were conducted using IBM SPSS Statistics 26. The results show high engagement with the SIMBALite application, with 88.37% of users reporting daily usage. The findings highlight that Facilitating Conditions significantly contribute to user satisfaction, underscoring the importance of providing adequate resources and support for effective technology use. The study also identifies areas for improvement, including enhancing support systems and addressing user experience factors. For BAZNAS, it is recommended to focus on improving the resources and support available to users to further enhance the application’s effectiveness. Future research should explore the long-term impact of technology adoption on organizational performance and investigate demographic variations in technology acceptance to gain deeper insights into user behavior.